Agency, Reciprocal Determinism, and Desistance from Crime: a Reply to Thomas, Pogarsky, and Loughran - Brezina, Timothy (Journal of developmental and life-course criminology, 2021)
In their rejoinder, Thomas, Pogarsky, Loughran come to the defense of Paternoster (2017) and promise to clarify his position. They also promise to elucidate the logical flaws associated with critiques of Paternoster’s position, reveal the fundamental incompatibility between agency and determinism, and advance the case for a teleological criminology. Although the authors help to clarify some aspects of Paternoster’s position, they ultimately fail to deliver on their promises. In this paper, I clarify my own position, challenge the agency/determinism dualism embraced by Thomas and his colleagues, and highlight additional problems with their approach, which appears to assume the existence of an autonomous and decontextualized willpower. In the end, I highlight the superior utility of a sociocognitive conceptualization of agency, which is rooted in the framework of reciprocal determinism. This conceptualization of agency is appealing for a variety of reasons. It lends itself to a humanistic approach as it provides a guide for human empowerment. When applied to criminological issues, such as desistance from crime, it can inspire new lines of inquiry. But most of all, it is rooted in science and is consistent with a large body of empirical evidence.